A tool for controlling accelerometers. Secondary calibration data - Juliani, Fernando; Barros, Everaldo de; Mathias, Mauro Hugo [UNESP] (Elsevier B.V., 2013)
Vibration monitoring requires acceleration transducers capable of providing data with high precision. Accelerometers are the most frequently used vibration transducers. Their calibration plays an important role in measuring vibrations and is a key component in ensuring the integrity of the vibration measurement. For managing secondary calibration data of accelerometers, a database computer system was implemented. The implementation of this software has been an important step forward in providing a wide range of analysis and display tools. This paper reviews the main concepts involving accelerometer secondary calibration and describes the tool developed and the methods used in its development. (C) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Accelerometer; Secondary calibration; Vibration testing; Database